School bullying: children and adolescent norms, cultures and identity development - Moody, Zoe; Stahel, Tina (Frontiers in Education, 2025)
IntroductionSchool bullying arises from a system of peers who form bonds through the repeated victimization of others. This empirical research article examines the function of bullying within the context of children and adolescent norms and cultures, aiming to highlight the motivations underlying inappropriate and anti-social behavior in school.MethodsThe study is a multi-method qualitative inquiry undertaken in one school system in Switzerland, including participants from the two main linguistic and cultural areas (French and German-speaking regions). Primary and secondary school students took part in focus groups (76 students) or seven individual interviews (7 students), while non-participant observations were carried out in seven primary school classes (185 students).ResultsThe findings indicate that when bullying occurs, it is mainly expected among peers, directly reflecting the prevailing but changing social norms within youth groups. They highlight how children and adolescent identity development is related to bullying.DiscussionThe article points to ways in which education actors can act when faced with anti-social behaviors or bullying situations.